Production of Pyomelanin, a Second Type of Melanin, via the Tyrosine Degradation Pathway in Aspergillus fumigatus - Schmaler-Ripcke, Jeannette (American Society for Microbiology (ASM), 2009)
Aspergillus fumigatus is the most important airborne fungal pathogen of immunosuppressed humans. A. fumigatus is able to produce dihydroxynaphthalene melanin, which is predominantly present in the conidia. Its biosynthesis is an important virulence determinant. Here, we show that A. fumigatus is able to produce an alternative melanin, i.e., pyomelanin, by a different pathway, starting from l-tyrosine. Proteome analysis indicated that the l-tyrosine degradation enzymes are synthesized when the fungus is grown with l-tyrosine in the medium. To investigate the pathway in detail, we deleted the genes encoding essential enzymes for pigment production, homogentisate dioxygenase (hmgA) and 4-hydroxyphenylpyruvate dioxygenase (hppD). Comparative Fourier transform infrared spectroscopy of synthetic pyomelanin and pigment extracted from A. fumigatus cultures confirmed the identity of the observed pigment as pyomelanin. In the hmgA deletion strain, HmgA activity was abolished and the accumulation of homogentisic acid provoked an increased pigment formation. In contrast, homogentisic acid and pyomelanin were not observed with an hppD deletion mutant. Germlings of the hppD deletion mutant showed an increased sensitivity to reactive oxygen intermediates. The transcription of both studied genes was induced by l-tyrosine. These results confirmed the function of the deleted genes and the predicted pathway in A. fumigatus. Homogentisic acid is the major intermediate, and the l-tyrosine degradation pathway leading to pyomelanin is similar to that in humans leading to alkaptomelanin.